New observations on the resistance of coconut cultivars to tropical cyclones in Vanuatu - Jean-Pierre LABOUISSE; Tiata SILEYE; Chantal HAMELIN (International Coconut Community, 2007)
The resistance of coconut palms to violent winds was observed at the Saraoutou research station as cyclone Dani passed over the island of Santo in Vanuatu in January 1999. Mortality caused by felling or uprooting was recorded on 13 Dwarf varieties, 10 Tall varieties and 28 Dwarf x Tall hybrids. The Dwarf palms were generally more susceptible than the Tall palms and hybrids, but substantial differences were also found between varieties in the same group. At 15 years old, the Tacunan Green Dwarf originating from the Philippines proved to be the most resistant Dwarf with 0% of felled palms compared to 100% of felled palms for the most susceptible, the Malayan Yellow Dwarf. Of the Tall palms, the Vanuatu Tall proved to be the most resistant with 2% of felled palms. The varieties originating from the South Pacific or the Philippines also displayed good resistance compared to varieties from Papua New Guinea. Of the hybrids, the Malayan Red Dwarf x Rennell Tall displayed the least resistance. The effect of different factors (morphological characteristics, age) on susceptibility to violent winds is discussed.